2000
DOI: 10.1074/jbc.m004079200
|View full text |Cite
|
Sign up to set email alerts
|

A Single Site (Ser16) Phosphorylation in Phospholamban Is Sufficient in Mediating Its Maximal Cardiac Responses to β-Agonists

Abstract: Phospholamban (PLB) can be phosphorylated at Ser 16by cyclic AMP-dependent protein kinase and at Thr 17 by Ca 2؉ -calmodulin-dependent protein kinase during ␤-agonist stimulation. A previous study indicated that mutation of S16A in PLB resulted in lack of Thr 17 phosphorylation and attenuation of the ␤-agonist stimulatory effects in perfused mouse hearts. To further delineate the functional interplay between dual-site PLB phosphorylation, we generated transgenic mice expressing the T17A mutant PLB in the cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
117
1
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(129 citation statements)
references
References 41 publications
(91 reference statements)
7
117
1
4
Order By: Relevance
“…Phosphorylation at both sites, Ser 16 and Thr 17 , relieves the inhibitory effect of PLB on SERCA and enhances SR Ca 2ϩ uptake, although the exact contribution of each phosphorylation site and its specific effect on heart function is not clear (3,6,9). Interestingly, in SERCA2 (ϩ/Ϫ) mice we found an increase in the phosphorylation status of PLB.…”
Section: Discussionmentioning
confidence: 54%
“…Phosphorylation at both sites, Ser 16 and Thr 17 , relieves the inhibitory effect of PLB on SERCA and enhances SR Ca 2ϩ uptake, although the exact contribution of each phosphorylation site and its specific effect on heart function is not clear (3,6,9). Interestingly, in SERCA2 (ϩ/Ϫ) mice we found an increase in the phosphorylation status of PLB.…”
Section: Discussionmentioning
confidence: 54%
“…In particular, PLB phosphorylation was decreased, which has been linked to dilated cardiomyopathy in humans (38) and associated with heart failure. However, the Pkd2 +/− mouse did not recapitulate phenotypes observed in mice with mutated PLB or troponin (39,40). Thus, the findings in the Pkd2 +/− mouse may reflect a compensatory pathway that has enabled an adaptation to altered calcium homeostasis without altering contractility through TnI phosphorylation.…”
Section: Discussionmentioning
confidence: 73%
“…However, we found that, in the absence of ␤AR activation, AC VI gene transfer alone increased PLB phosphorylation on serine 16 ( Fig. 1, top 16) phosphorylation has been shown to be sufficient in mediating its maximal cardiac responses to ␤-agonists (13). The following studies were focused on determining the mechanisms for AC VI -associated Ser-16 phosphorylation of phospholamban.…”
Section: Resultsmentioning
confidence: 99%